A hybrid strategy for mapping multiple throughput-constrained applications on MPSoCs - Singh, Amit Kumar; Kumar, Akash; Srikanthan, Thambipillai (Proceedings of the 14th International Conference on Compilers, Architectures and Synthesis for Embedded Systems, 2011)
Modern embedded systems are based on Multiprocessor-Systems-on-Chip (MPSoCs) to meet the strict timing deadlines of multiple applications. MPSoC resources must be utilized efficiently by mapping the applications in throughput-aware manner in order to meet throughput constraints for each of them. A design-time methodology is applicable only to predefined set of applications with static behavior, which is incapable of handling dynamism in applications. On the other hand, a run-time approach can cater to the dynamism but cannot provide timing guarantees for all the applications due to large computation requirements at run-time. This paper presents a hybrid flow which performs compute intensive analysis at design-time to derive multiple resource-throughput trade-off points and selects one of these at run-time subject to available resources and desired throughput. Experimental results show that the design-time analysis is faster by 39%, provides better trade-off points and the run-time mapping is speeded up by 93% when compared to state-of-the-art techniques.